2015
DOI: 10.3923/ajas.2015.233.240
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Escherichia coli Isolated from Beef and its Related Samples in Techiman Municipality of Ghana

Abstract: In the present study, antibiotic susceptibility test was performed using the disc diffusion method and the results interpreted using the Clinical and Laboratory Standards Institute guidelines. A total of 45 Escherichia coli isolates were screened against nine different antibiotics. Overall, 34.57% of the Escherichia coli isolates were resistant, 7.16% were intermediate and 58.27% were susceptible. Resistance to vancomycin (88.89%) and erythromycin (68.89%) was high. Susceptibility to ciprofloxacin (95.56%), am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 16 publications
8
24
1
Order By: Relevance
“…The result obtained for the antimicrobial susceptibility test is shown in Table 1. From Table 1, the (Adzitey et al, 2012b;Adzitey, 2015). It is also indicated that in clinical diagnoses patients with intermediate results can be given a higher dosage of antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result obtained for the antimicrobial susceptibility test is shown in Table 1. From Table 1, the (Adzitey et al, 2012b;Adzitey, 2015). It is also indicated that in clinical diagnoses patients with intermediate results can be given a higher dosage of antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Res. Bacteriol., 8 (2): 34-40, 2015 Researches in the antibiotic susceptibility of Escherichia coli and other food/waterborne pathogens in Ghana are limited and the few researches available have concentrated more on human isolates (Adzitey, 2015). Saba and Tekpor (2015) in their work determined the antibiotic resistance patterns of Escherichia coli O157: H7 isolated from swimming pools and found that, the Escherichia coli were resistant to ceftriaxone (25%), chloramphenicol (21%), amoxycillin-clavulanic acid (14%), ciprofloxacin (11%) and gentamicin (4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different resistance patterns were observed against different antibiotics ( Table 3 ). The MAR index of the isolates (which ranged from 0.1 to 0.6) also revealed the contamination level and health risks at the sample collection sites [34] , [35] .…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, there are fewer reports on antibiotic resistance of foodborne pathogens. The few studies available have also concentrated much on foodborne pathogens isolated from animals and humans (Mills-Robertson et al 2002;Awua-Boateng 2007;Nsoah, 2015;Donkor et al 2012;Adzitey 2015a;Adzitey et al 2015;Andoh et al 2016). However, vegetables in Ghana, including cabbages and lettuces are important sources of resistant foodborne pathogens and should not be ignored.…”
Section: Introductionmentioning
confidence: 99%